Injection of high dose botulinum-toxin A leads to impaired skeletal muscle function and damage of the fibrilar and non-fibrilar structures. Issue 1 (December 2017) - Pingel, Jessica; Nielsen, Mikkel; Lauridsen, Torsten; Rix, Kristian; Bech, Martin; Alkjaer, Tine; Andersen, Ida; Nielsen, Jens; Feidenhansl, R.
Abstract Botulinum-toxin A (BoNT/A) is used for a wide range of conditions. Intramuscular administration of BoNT/A inhibits the release of acetylcholine at the neuromuscular junction from presynaptic motor neurons causing muscle-paralysis. The aim of the present study was to investigate the effect of high dose intramuscular BoNT/A injections (6 UI = 60 pg) on muscle tissue. The gait pattern of the rats was significantly affected 3 weeks after BoNT/A injection. The ankle joint rotated externally, the rats became flat footed, and the stride length decreased after BoNT/A injection. Additionally, there was clear evidence of microstructural changes on the tissue level by as evidenced by 3D imaging of the muscles by Synchrotron Radiation X-ray Tomographic Microscopy (SRXTM). Both the fibrillar and the non-fibrillar tissues were affected. The volume fraction of fibrillary tissue was reduced significantly and the non-fibrillar tissue increased. This was accompanied by a loss of the linear structure of the muscle tissue. Furthermore, gene expression analysis showed a significant upregulation of COL1A1, MMP-2, TGF-b1, IL-6, MHCIIA and MHCIIx in the BoNT/A injected leg, while MHVIIB was significantly downregulated. In conclusion: The present study reveals that high dose intramuscular BoNT/A injections cause microstructural damage of the muscle tissue, which contributes to impaired gait.